1999
DOI: 10.1177/107155769900600307
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Fluid Cytokine and Eicosanoid Levels and Their Relation to the Incidence of Peritoneal Adhesion

Abstract: Objective: To determine the peritoneal fluid content of several cytokines and eicosanoids with inflammatory, anti-inflammatory, anti-fibrotic, and fibrotic activities, and to assess the relationship of these levels with the incidence of peritoneal adhesions. Methods: Peritoneal fluids were collected from 30 subjects with adhesions (n = 22) or with normal pelvic anatomy (n = 8), and the level of interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-α), interleukin-10 (IL-10), interferon gamma (IFN-γ), trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
8
1
1
Order By: Relevance
“…Of note is the observation that PM responded to TLR ligands in an identical manner as did AM. Peritoneal fluids from normal humans have been shown to contain IL-10 in the range from 6 to 10 pg/ml (30,31), which is substantially lower than what we observed in normal murine BALF. However, PM are also not normally exposed to environmental particulates or microorganisms as are AM, so whether TLR-mediated IL-10R dysfunction in PM has a physiologic role in the peritoneum is not known.…”
Section: Discussioncontrasting
confidence: 52%
“…Of note is the observation that PM responded to TLR ligands in an identical manner as did AM. Peritoneal fluids from normal humans have been shown to contain IL-10 in the range from 6 to 10 pg/ml (30,31), which is substantially lower than what we observed in normal murine BALF. However, PM are also not normally exposed to environmental particulates or microorganisms as are AM, so whether TLR-mediated IL-10R dysfunction in PM has a physiologic role in the peritoneum is not known.…”
Section: Discussioncontrasting
confidence: 52%
“…Several in vitro and in vivo findings ascertain the antifibrogenic effect of IFN-g. For example, IL-10 inhibits IFN-g expression in most cell systems, and adhesion tissues have been shown to contain a significantly lower amount of IFN-g and a higher amount of IL-10 as compared with normal peritoneal tissue. 134 Our group has shown that expression of IFN-g was significantly reduced with the simultaneous increase in IL-10 expression in adhesion fibroblasts under hypoxic conditions. 66 We have also shown that IFN-g can block the effects of hypoxia on apoptosis.…”
Section: Possible Role Of Enzymes Polypeptides and Antioxidants In mentioning
confidence: 99%
“…It is well established that MMP and TIMP expression is highly regulated at transcriptional and translational levels, and is modulated by several growth factors, cytokines and hormones 14,23,25,28,38 . Many of these growth factors and cytokines are expressed by the tissues used in our study and are present in the peritoneal fluid 9,10,30,32,39,41,42 . For instance, TGF-h, which induces peritoneal adhesion formation and fibrosis in many other tissues, differentially regulates the expression of MMPs, TIMPs and ECM, a mechanism that mediates TGF-h-induced tissue MMP-3 AND TIMP-2 EXPRESSION IN PERITONEAL SEROSAL TISSUE AND ADHESIONS 1047 fibrosis 4,5,9,32 .…”
Section: Discussionmentioning
confidence: 99%